High Throughput Screening for New Fungal Polyester Hydrolyzing Enzymes - Weinberger, Simone; Beyer, Reinhard; Schüller, Christoph; Strauss, Joseph; Pellis, Alessandro; Ribitsch, Doris; Guebitz, Georg M. (Frontiers in Microbiology, 2020)
There is a strong need for novel and more efficient polyester hydrolyzing enzymes in order to enable the development of more environmentally friendly plastics recycling processes allowing the closure of the carbon cycle. In this work, a high throughput system on microplate scale was used to screen a high number of fungi for their ability to produce polyester-hydrolyzing enzymes. For induction of responsible enzymes, the fungi were cultivated in presence of aliphatic and aromatic polyesters (poly(1,4-butylene adipate co terephthalate) (PBAT), poly(lactic acid) (PLA) and poly(1,4-butylene succinate) (PBS)), and the esterase activity in the culture supernatants was compared to the culture supernatants of fungi grown without polymers. The results indicate that the esterase activity of the culture supernatants was induced in about 10% of the tested fungi when grown with polyesters in the medium, as indicated by increased activity (to >50 mU/mL) towards the small model substrate para-nitrophenylbutyrate (pNPB). Incubation of these 50 active culture supernatants with different polyesters (PBAT, PLA, PBS) led to hydrolysis of at least one of the polymers according to liquid chromatography-based quantification of the hydrolysis products terephthalic acid, lactic acid and succinic acid respectively. Interestingly, the specificities for the investigated polyesters varied among the supernatants of the different fungi.